The Influence Of Work-Life Balance And Job Stress On Job Satisfaction Mediated By Burnout In Generation Z Employees In The Maufacturing Sector MM2100 - Lestari, Putri Ayu; Retno Purwani Setyaningrum (SEAN Institute, 2024)
Satisfaction at work is an important role for the sustainability of an organization. In creating job satisfaction, organizations must pay attention to the quality of employees because satisfaction at work is one of the standards for employees who provide work and for the company where they work. The goal of this research is to determine the influence of work-life balance and work stress on job satisfaction with burnout as a mediating variable. This research used a quantitative method using Generation Z employees in the MM2100 manufacturing sector with a total of 96 respondents as the sample. This research was processed using SmartPLS data processing software and data collection was carried out using Google formulas. This research shows that there is a significant positive influence between work-life balance on the satisfaction of generation z employees in the MM2100 manufacturing sector, there is a positive and significant influence between work stress on the job satisfaction of generation z employees in the MM2100 manufacturing sector, there is a negative and significant influence There is a significant relationship between burnout and job satisfaction of generation z employees in the Manufacturing sector MM2100, there is a negative and significant influence between work-life balance and burnout, there is a negative and significant influence between work stress and burnout of generation z employees in the manufacturing sector MM2100, burnout can mediate work-life balance and work stress positively and significantly influence the job satisfaction of generation z employees in the MM2100 manufacturing sector. Job satisfaction has an impact on all activities within the company, so that it becomes an aspect that requires special attention from company management. Work-life balance has an influence on the job satisfaction of generation z employees in the MM2100 manufacturing sector.